MOST ESSENTIAL POINTS IN TEACHING LANGUAGES - Numanova Mashxura Qobiljon qizi (Scholars Digest Publishing, 2023)
English is often considered one of the most difficult languages to learn fluently, if you haven’t grown up speaking it. As a second language, mastering secondary level English can be a challenge, but helping your students gain a strong command of the language is far from impossible. In this article most essential points of teaching methods are discussed.
Keywords: approach, debate, encourage, fluently, effective, skill, practice, motivation, technique, environment.